Alienação parental: uma explicação pautada em traços de personalidade e nos valores humanos - Carvalho, Thayro Andrade (2015)
This dissertation aimed to know if the personality traits and human values are able to explain the maternal alienating practices. Specifically, we intended to: (1) develop and know the psychometric parameters of the Inventory of Maternal Alienating Practices (IMAP); (2) verify the confirmatory validity of IMAP; and (3) test an explicative model, in which the personality traits and values are predictors of maternal alienating practices. Thus, we developed three studies with correlational design, ex post facto, and quantitative methodology. In study 1, we aimed to build and know the psychometric parameters of IMAP. Participants were 200 divorced mothers, aged 22-66 (M = 37.12 years, SD = 9.06). After testing the discriminative power of 13 initial items using a Student t test, remained Twelve. Then we proceeded to a factor analysis, identifying, using the PA criterion, a structure composed of a single factor, with all items showing loadings higher than |.30| and Cronbach's alpha of .83. In Study 2, we carried out a Confirmatory Factor Analysis (CFA) of IPMA. Counted on a sample by intentional convenience of 189 divorced mothers, aged 20-70 years (M = 37.8, SD = 10.69). The results of the AFC after removal of two items (6 and 11) showed marginally acceptable indicators [χ² = 141.05, χ²/gl = 4.03, GFI = .87, AGFI = .80, CFI = .88 and RMSEA (IC90 % = .12 – .10) = .14, CAIC = 265.89 e ECVI = .96], satisfactory level of internal consistency α = .88, so as the composite commonality (CC = .90) and mean variance explained (VME = .50). It is considered therefore that the objectives of the previous studies have been achieved, given a quality metric of the instrument developed. In Study 3, in an attempt to propose an explanatory model of maternal alienating practices, we sought to identify the correlation between these practices and the personality traits and human values, and also verify the predictive power of these constructs against these practices. Participants were 188 divorced mothers, aged 17-61 years (M = 32.2 years, SD = 9.17). Were performed Pearsons correlation, linear regression to assess predictive power, as has also been proposed a hierarchical model through the software AMOS. The main results indicate that personality trait kindness and values subfunction suprapersonal present correlation with the amaternal alienating practices (r = -.18; p <.05 and r = -.24, p <.05, respectively). From these results, it was found the predictive power of these variables towards the maternal alienating practices, noting its predictor potential front practices satisfactorily. Taking these results as a basis, we tested an explicative model, in which the kindness trait was able to predict the suprapersonal subfunction which jointly explained maternal alienating practices. Thus, the hierarchical model personality traits → values → maternal alienating practices presents satisfactory quality at the adjustments indices, shown through structural equation modeling. In conclusion, the present dissertation objectives were achieved, emphasizing the theoretical framework used for identifying robustly that factors associated with loving characteristics and emotional balance, can consistently help to understand maternal alienating practices.